Alpha 1 antitrypsin deficiency due to Pi null: clinical presentation and evidence for molecular heterogeneity. Issue 2 (February 1988) - Bamforth, F J; Kalsheker, N A
Abstract : The proteinase inhibitor null (Pi-) allele is a rare cause of alpha 1 antitrypsin (AAT) deficiency. In three families, all the subjects with AAT deficiency due to PiZ- presented in early childhood with recurrent chest infections and wheezing presumably related to passive smoking. In Pi- the AAT gene is present and there is no evidence for a gene deletion. In one family a restriction fragment length polymorphism (RFLP) detected with the enzyme XbaI segregates with the Pi- allele. In a family where a consanguineous marriage occurred, the XbaI polymorphism segregates with the normal M1 allele rather than Pi-, suggesting that Pi- may have originated from M1. In contrast, a third family and 20 normal unrelated subjects do not show the RFLP.